2017
DOI: 10.1021/acs.energyfuels.7b02274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Clay Minerals on Heavy Oil Oxidation during Ignition Process

Abstract: During the procedure of in situ combustion (ISC) for heavy oil, the rate of heat release at the low temperature oxidation (LTO) stage directly affects the delay time and the effect of ignition. This paper aimed at various clay minerals effects on heavy oil oxidation before ignition, at different reservoir temperatures and air/oil ratios, using a small batch reactor (SBR). Characterizations of the pressure, the reaction temperature, the post-test gases, the viscosity, and the asphalt content of heavy oil before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Works regarding the in situ combustion of heavy oils have also reported the impact of kaolinite in enhancing reaction rates and influencing product composition. 16,90 However, the rapid deactivation of kaolinite due to the deposition of carbonaceous material during conversion and the low surface area of kaolinite meant that the potential catalytic contribution of kaolinite was limited. Therefore, although kaolinite performed acid-catalyzed reactions, its impact on the overall conversion during petroleum processing is likely to be minor due to the fast deactivation of the mineral.…”
Section: Catalytic Effect Of Minerals On Ams Conversionmentioning
confidence: 99%
“…Works regarding the in situ combustion of heavy oils have also reported the impact of kaolinite in enhancing reaction rates and influencing product composition. 16,90 However, the rapid deactivation of kaolinite due to the deposition of carbonaceous material during conversion and the low surface area of kaolinite meant that the potential catalytic contribution of kaolinite was limited. Therefore, although kaolinite performed acid-catalyzed reactions, its impact on the overall conversion during petroleum processing is likely to be minor due to the fast deactivation of the mineral.…”
Section: Catalytic Effect Of Minerals On Ams Conversionmentioning
confidence: 99%
“…A series of experiments were conducted to understand coke formation under different reaction conditions , and the presence of montmorillonites and nanoparticles . Yu et al in 2017 concluded that clay could accelerate reaction rates and improve an ignition process . Metal nanoparticles and metal tallates were tested to improve the performance of in situ combustion.…”
Section: Css Follow-up Processes and Simulationmentioning
confidence: 99%
“…Because of its low cost and less energy consumption, the ISC technology is labeled as a promising technique for heavy and extra-heavy oil recovery from reservoirs. , With all these advantages, ISC still suffers from some drawbacks such as the difficult initiation point of ignition and unstable combustion point in porous media in order to achieve oil displacement for enhanced oil recovery. , There are several methods to overcome these disadvantages including in situ combustion process in the presence of catalysts and in situ combustion in the presence of water or steam. ,, …”
Section: Introductionmentioning
confidence: 99%